ADMINISTRATION EXPENSES AS A COMPONENT OF ENTERPRISE MANAGEMENT - Zhuk О.I. (The actual problems of regional economy development, 2016)
In the article the features of an object cost management, the basic principles and functions of management costs. The effect on cost management and efficiency of successful management. The place cost management company in the management of financial and economic activity of the enterprise. JEL: M 20